Perbedaan Tingkat Pengetahuan, Sikap dan Perilaku Hidup Bersih dan Sehat (PHBS) Ibu dengan Kejadian Diare pada Balita di WIlayah Kerja Puskesmas Seyegan, Sleman - Hastomo Hastomo; Sri Muryani; Haryono Haryono (Sanitasi: Jurnal Kesehatan Lingkungan, 2009)
As an environmental based disease, diarrhea frequently attacks infant and under five children. The total diarrhea incidences troughout 2008 in SeyeganCommunity Health Centre were more than 800 cases. The study was to understood the correlation between mothers’ level of knowledge, attitude and practice on healthy and clean behaviours (PHBS) with diarrhea incidence of their underfive children. The study was an observational one with case control design. The case group consisted of 46 children who were diagnosed of diarrhea in the last two months, meanwhile the control group comprised with other 46 undiagnosed children. A valid and reliable piloted questionnaire and check-list were used to measure the predictor factors. The study showed that in the control group, the level of knowledge, attitude and practice on PHBS were significantly higher than those in case group.